Intercultural coexistence: The last frontier? - DÍAZ MONTIEL , Zulay (Utopía y Praxis Latinoamericana, 2022)
The political ideal of today’s society is to achieve intercultural social integration that can guarantee well-being and peace through solidarity. These are two principles of hope of great ethical value for citizens who participate jointly in public life and private life. But the achievement of a subsidiary society of common goods for all and guarantor of social peace, requires a set of duties and rights enshrined in standards to be fulfilled for all on equal terms, which could be validated from: i) a practical speech ethical-moral, that is in solidarity with the other in intercultural terms; and ii) individual and collective actions, whose interests are committed to that good life that you want to share in equal conditions.